To illustrate storybook of marbled cats / Muhammad Uzayr Hiu Muhammad Yusuf Hiu - Muhammad Yusuf Hiu, Muhammad Uzayr Hiu (2022)
The purpose of this study was to emphasize to the community the importance of marbled cats are almost extinct due to the damage factors that occur in the forest. From the research that was studied, a researcher needs to complete this research to aware children and help marbled cats from extinction. The question research for the topic is what is the solution in order to introduce the speciality of marbled cat in Malaysia and what is the appropriate story telling that suitable for kindergarten student in Malaysia. Next is the objective is to introduces the marbled cat as one of the special cat species in Malaysia through kindergarten story book. The second objective is to create an appropriate base in moral story approach of story book among kindergarten. In order to accomplish the research of this topic is using the quantitative method to collect percentages of data by a survey about the research. It is also had required supporting data by collecting from articles or internet resources.